2022
DOI: 10.3389/fchem.2022.1004269
|View full text |Cite
|
Sign up to set email alerts
|

Improved solid-phase microextraction extraction procedure to detect trace-level epichlorohydrin in municipal water systems by HS-SPME-GC/MS

Abstract: Epichlorohydrin (ECH) is toxic to humans via multiple routes and is a potential carcinogen. The accurate measurement of ECH at trace level (<0.1 μg/L) is still an obstacle hindering the monitoring and regulation of municipal water systems. In this study, an improved headspace solid-phase microextraction (HS-SPME) procedure is developed and optimized to extract and enrich ECH with high sensitivity, accuracy, and precision. A total 17.4-time enhancement in extraction efficiency is achieved compared with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…The dependence of water pH on recovery is not suspected to be an important parameter, given the nonpolarizable nature of OCPs, but has been evaluated by Frenich et al (2011) and Qiu & Cai (2009). The addition of salt to the sample ideally to make analytes less soluble and more volatile has been evaluated by Frenich et al (2011), Antelo et al (2007), Mmualefe et al (2009), Qiu & Cai (2009), Holopainen et al (2013), Martínez et al (2013), and Lei et al (2022), with little effect found for OCPs. A variety of fiber coatings and coating thicknesses have been evaluated by Alonso et al (2003), Polo et al (2005), Derouiche et al (2007), Mmualefe et al (2009), Qiu & Cai (2009), and Martínez et al (2013).…”
Section: Introductionmentioning
confidence: 99%
“…The dependence of water pH on recovery is not suspected to be an important parameter, given the nonpolarizable nature of OCPs, but has been evaluated by Frenich et al (2011) and Qiu & Cai (2009). The addition of salt to the sample ideally to make analytes less soluble and more volatile has been evaluated by Frenich et al (2011), Antelo et al (2007), Mmualefe et al (2009), Qiu & Cai (2009), Holopainen et al (2013), Martínez et al (2013), and Lei et al (2022), with little effect found for OCPs. A variety of fiber coatings and coating thicknesses have been evaluated by Alonso et al (2003), Polo et al (2005), Derouiche et al (2007), Mmualefe et al (2009), Qiu & Cai (2009), and Martínez et al (2013).…”
Section: Introductionmentioning
confidence: 99%